Marketing Public Relations di Instagram Happy Go Lucky House - Alethea Salsabila Muntazzahra; Indri Rachmawati (UNISBA Press, 2023)
Abstract. The use of Instagram to do digital marketing has been widely used by various companies to promote their merchandise. To do digital marketing, the role of a Marketing Public Relations person who understands business competition is needed. Marketing Public Relations takes advantage of the current situation by using social media which can later take advantage of the features on social media. Happy Go Lucky House uses Instagram as one of the Public Relations Marketing processes. The purpose of this study is to determine the activities, roles, and techniques used on Instagram as a Marketing Public Relations process. In this study, researchers used the theory of new media theory, promotion mix theory, and PESO model. Researchers use qualitative methods with a case study approach, namely that they want to explore information in depth, especially the use of Instagram as a Marketing Public Relations process. Data collection techniques carried out in this study used interviews, observations, written sources and documentation. Key informants In testing the validity of the data here researchers use source triangulation and source triangulation. The subject of the research or key informant in this study is the internal party of Happy Go Lucky, namely the Marketing Team and the content creator team, while the supporting speakers are followers of Happy Go Lucky's Instagram and brand owners who collaborate with Happy Go Lucky. The results of this study show that there are activities carried out by utilizing the features available as promotional media, then the role of Instagram, namely to make Happy Go Lucky more known and there are certain techniques in the use of Instagram, namely to increase engagement and also bind consumers. Abstrak. Pemanfaatan Instagram untuk melakukan pemasaran secara digital sudah banyak dimanfaatkan oleh berbagai perusahaan untuk mempromosikan barang dagangannya. Untuk melakukan pemasaran secara digital dibutuhkannya peran seorang Marketing Public Relations yang mengerti tentang persaingan bisnis. Marketing Public Relations memanfaatkan situasi seperti sekarang ini dengan cara menggunakan media sosial yang nantinya bisa memanfaatkan fitur-fitur di sosial media tersebut. Happy Go Lucky House memanfaatkan Instagram sebagai salah satu proses Marketing Public Relations. Tujuan penelitian ini untuk mengetahui aktivitas, Peran, dan Teknik-teknik yang digunakan di Instagram sebagai proses Marketing Public Relations. Dalam penelitian ini peneliti menggunakan teori teori new media, teori promotion mix, dan model PESO. Peneliti menggunakan metode kualitatif dengan pendekatan studi kasus, yaitu itu ingin menggali informasi secara mendalam khususnya pemanfaatan di Instagram sebagai proses Marketing Public Relations. Teknik pengumpulan data yang dilakukan dalam penelitian ini menggunakan wawancara, observasi, Sumber tertulis dan Dokumentasi. Key informan Dalam menguji keabsahan data disini peneliti menggunakan triangulasi sumber dan triangulasi narasumber. Subjek Penelitian/Key informan dalam penelitian ini ialah pihak internal Happy Go Lucky yaitu Tim Marketing dan tim content creator, sedangkan untuk narasumber pendukung yaitu followers dari Instagram Happy Go Lucky dan pemilik brand yang bekerjasama dengan Happy Go Lucky. Hasil dari penelitian ini menunjukkan adanya aktivitas yang dilakukan dengan cara memanfaatkan fitur yang tersedia sebagai media promosi lalu adanya peran Instagram yakni untuk membuat Happy Go Lucky menjadi lebih dikenal dan terakhit adanya Teknik-teknik tertentu dalam pemanfaatan Instagram ini yaitu untuk menaikkan engagement juga mengikat konsumen.